Effect of Hormonal Changes Through 7 Days of Osho Dynamic Meditation Among Healthy Nepalese Participants - Vijay Kumar Sharma; Apeksha Niraula; Eans Tara Tuladhar; Raju Kumar Dubey; Aseem Bhattarai; Mithileshwer Raut; Nikita Kharal; Anuradha Kadel; Srijana Sapkota; Prakash Pokhrel; Namrata Sharma (Wiley, 2024)
ABSTRACT Context Meditation and related relaxation techniques are good means of alleviating stress and maintaining good health. Osho dynamic meditation decreases several psychopathological variables such as anxious‐depressive syndrome, aggressive behaviors, and depression which is practiced in Nepal and all over the world. Various studies have shown alteration in different hormone levels due to meditation by strengthening adaptive mechanisms. Aim The aim of this study was to evaluate the effect of Osho meditation on serum hormonal levels in pre‐ and postmeditation participants. Methods A pre-post study was conducted among 70 healthy volunteers (42 male and 28 female) where various types of Osho dynamic meditation techniques were incorporated together to understand their combined effects on serum hormone levels in participants attending the 7 days meditation camp. Serum hormones such as cortisol, estrogen, progesterone, free triiodothyronine (fT3), free thyroxine (fT4), thyroid‐stimulating hormone (TSH), testosterone, and growth hormone were measured by chemiluminescence immunoassay. Results Out of 70 participants, 68 participants (97%) had subjective opinion of Osho dynamic meditation being effective in alleviating stress, depression, and anger. Also, there was a significant decline in body weight and body mass index in both male and female populations after a strict vegetarian diet and meditation. Likewise, a significant rise in the level of estrogen (p < 0.001), progesterone (p < 0.001), growth hormone (p < 0.001), testosterone (p = 0.002), and fT3 (p = 0.049) in postmeditation male participants indicates the importance of Osho dynamic meditation on elevating sex hormones such as estrogen, progesterone, testosterone as well as fT3, and growth hormones among Osho meditation practicing participants. Conclusion Our findings suggest significant changes in the hormonal levels and improvement in stress and depression in participants undergoing Osho meditation.